Test/Re-Test reliability of the readiness for interprofessional education learning scale and interdisciplinary education perception scale in health science students. - Sciascia, Aaron; Christopher, Karina; Humphrey, Casey; Simpkins, Leah; Page, Christen Guffey; Jones, Lisa G. (Journal of Interprofessional Care)
This study aimed to establish the test/re-test reliability of two common interprofessional education (IPE) instruments, the Readiness for Interprofessional Learning Scale (RIPLS) and the Interdisciplinary Education Perception Scale (IEPS), and to compare results based on previous IPE experience. The RIPLS and the IEPS were distributed to 251 students within five academic health science programs at one university. Both instruments were distributed at a second session 10–14 days later. Weighted Kappa, intraclass correlation coefficients (ICC), standard error of measurement, and minimal detectable change were calculated for each instrument's composite scores and subscales. Assessments occurred for all subjects and between students with and without previous IPE experience. Overall and between-group composite score reliability for the RIPLS and IEPS were excellent (ICC≥0.81). RIPLS subscale ICCs were variable per previous IPE experience, ranging from fair-excellent (ICC = 0.56–0.86). IEPS subscale ICCs were excellent for students with previous IPE experience (ICC≥0.76), and fair-excellent for students without previous experience (ICC = 0.64–0.84). Students with previous IPE experience had significantly higher scores within and between sessions for the RIPLS (p ≤ 0.031) but not the IEPS. Both instruments have acceptable measurement consistency; however, the RIPLS varied in repeatability compared to the IEPS. Previous IPE experience should be accounted for when distributing/interpreting the results.